The Impact of Baitul Maal wa Tamwil on Household Welfare: Empirical Evidence from Indonesia - Astuti, Riska Dwi; Samir, Salman (Jurnal Ekonomi & Studi Pembangunan, 2021)
Despite the growing studies of Baitul Maal wa Tamwil (BMT) in Indonesia, few have empirically analyzed how BMT increases household welfare, primarily through credit for productive activities. This study aimed to analyze the impact of BMT availability in the community on household welfare. Considering that credit is targeted for productive activities, the researchers limited the respondents to farmer households and households with non-farming business activities, amounting to 4642 and 2250, respectively. Utilizing longitudinal data from the Indonesian Family Life Survey (IFLS), the analysis was conducted employing the difference-in-difference (DiD) method. The results showed that BMT's existence in the community improved farmer households' mean welfare by 1.65%. After controlling for household and community characteristics, consistent results were obtained with a small decrease in the coefficient of 1.58%. Meanwhile, households with non-farming business activities were not affected by the existence of BMT in their community. Nevertheless, a positive coefficient of diff-in-diff indicated that BMT and welfare had a positive relationship even though it was not strong enough to be a contributor to the outcome.